Spiral Batik with Rational Bezier Curve - Khairiah Razali, Noor; Musliha Nor-Al-Din, Siti; Mohamad Sukri, Nursyazni; Izhar Ishak, Muhammad; Abdul Hadi, Normi (International Journal of Engineering and Technology, 2018)
Spiral is one of the commercial designs that is used in designing Batik patterns. There are many types of spiral motifs that can be designed for beautiful batik patterns. In this paper, one of the spiral shapes was chosen as a reference figure to regenerate using quadratic and cubic rational Bezier curves. This curve is well known as areas of research in Computer Aided and Geometric Design (CAGD). This paper deals with generating the spiral batik design and manipulation of weight magnitude to regenerate the design that is closer to the reference figure and produce new and variety designs by manipulating the value of weight in the curve. From the result, it shows that the cubic curve generated the spiral batik design was closer to the reference figure and produced more designs of the spiral Batik compared to the quadratic curve. The result also shows that quadratic Bezier curve is suitable to be used in generating the design since it involves simple and less cost method by manipulating a variable which is the weight in the curve. Lastly the result shows.Â  Conclusively, this method improves the batik industry by using CAGD in designing the motif.Â Â